2021
DOI: 10.1016/j.jamda.2020.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning in Asia: A Systematic Narrative Review of Healthcare Professionals’ Knowledge, Attitude, and Experience

Abstract: Objective: The value of advance care planning (ACP) for patients with life-limiting illnesses is widely recognized but Asian health care professionals' (HCPs') perspectives on ACP have received little systematic attention. We aim to synthesize evidence regarding Asian HCPs' knowledge of, attitudes toward, and experiences with ACP. Design: Systematic review with narrative synthesis and stepwise thematic analysis. Setting and Participants: HCPs in southern, eastern, and southeastern Asia. Methods: Studies from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 75 publications
3
82
0
6
Order By: Relevance
“…A systematic review of the English-language articles on ACP in Asia including Japan, available on Embase, MEDLINE, Web of Science, and Google Scholar, has been reported. [ 13 ] The findings were integrated using a narrative synthesis because it has the distinction of being able to adopt a textual approach to the process of integration to “tell the story” of the findings from the studies it contains, as well as being able to involve the manipulation of statistical data. [ 14 ]…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of the English-language articles on ACP in Asia including Japan, available on Embase, MEDLINE, Web of Science, and Google Scholar, has been reported. [ 13 ] The findings were integrated using a narrative synthesis because it has the distinction of being able to adopt a textual approach to the process of integration to “tell the story” of the findings from the studies it contains, as well as being able to involve the manipulation of statistical data. [ 14 ]…”
Section: Methodsmentioning
confidence: 99%
“…4,5 In our systematic review of Asian healthcare professionals’ perspectives on advance care planning, we found that professionals regard families as playing the leading role in it. 6 However, we also observed that these professionals rarely engage patients in advance care planning, even when the patients retain their decision-making capacity. Among the reasons for not engaging patients was healthcare professionals’ concern about patients’ lack of readiness to engage in advance care planning.…”
Section: Introductionmentioning
confidence: 82%
“…For persons with dementia, the long trajectory towards the end of life encompasses complex care needs that require continuity and coordination of care across health and social care services. Therefore, we recommend policy that enables proactive end-of-life care planning that is integrated into health and social care reforms [ 41 ].…”
Section: Discussionmentioning
confidence: 99%